Hubungan antara Self-esteem dan Self-compassion dengan Resiliensi pada Mahasiswa Tahun Pertama Perkuliahan - Adinda Amelia Fitriani; Mochamad Widjanarko (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examined the relationship between self-esteem and self-compassion with resilience among first-year university students. A quantitative approach was employed with 100 first-year students at Universitas Muria Kudus who completed online questionnaires assessing resilience, self-esteem, and self-compassion. Data were analyzed using multiple linear regression and Spearman’s Rho correlation in SPSS 27.0. The results showed that self-esteem and self-compassion jointly had a highly significant positive relationship with resilience (r = 0.721; p < 0.01), explaining 52.16% of the variance in resilience. Individually, self-esteem demonstrated a strong positive relationship with resilience (r = 0.719; p < 0.01), whereas self-compassion showed a moderate but still significant positive relationship (r = 0.526; p < 0.01). These findings indicate that higher levels of self-esteem and self-compassion are associated with stronger adaptive capacity and greater emotional stability among first-year students when facing academic and social challenges during the transition to university life. Overall, this study highlights the importance of strengthening internal psychological resources as protective factors for resilience in emerging adulthood. The results also suggest that well-being programs designed to foster self-worth, self-acceptance, and compassionate attitudes toward oneself may contribute to improved adjustment, academic persistence, and mental health among first-year university students. In conclusion, higher education institutions are expected to design psychological intervention programs that focus on strengthening the internal aspects of new students. The implementation of these programs should be carried out in an integrative manner, not only oriented towards boosting self-esteem through academic achievement, but also including self-compassion training to build students' emotional stability in facing pressure.